Formation of Mono Oxo Molybdenum(IV) PNP Pincer Complexes: Interplay between Water and Molecular Oxygen. Issue 7 (12th February 2018) - de Aguiar, Sara R. M. M.; Öztopcu, Özgür; Troiani, Anna; de Petris, Giulia; Weil, Matthias; Stöger, Berthold; Pittenauer, Ernst; Allmaier, Günter; Veiros, Luis F.; Kirchner, Karl
Abstract : The synthesis of cationic mono oxo Mo IV PNP pincer complexes of the type [Mo(PNP Me ‐ i Pr)(O)X] + (X = I, Br) from [Mo(PNP Me ‐ i Pr)(CO)X2 ] is described. These compounds are coordinatively unsaturated and feature a strong Mo≡O triple bond. The formation of these complexes proceeds via cationic 14e intermediates [Mo(PNP Me ‐ i Pr)(CO)X] + and requires both molecular oxygen and water. ESI MS measurements with 18 O labeled water (H2 18 O) and molecular oxygen ( 18 O2 ) indicates that water plays a crucial role in the formation of the Mo≡O bond. A plausible mechanism based on DFT calculations is provided. The X‐ray structure of [Mo(PNP Me ‐ i Pr)(O)I]SbF6 is presented. Abstract : The synthesis of cationic mono oxo Mo IV PNP pincer complexes of the type [Mo(PNP Me ‐ i Pr)(O)X] + (X = I, Br) is described. These compounds are coordinatively unsaturated and feature a strong Mo≡O triple bond. Their formation requires cooperation between molecular oxygen and water.